The Effect of Earnings Management, Board Characteristics, and Firm Size to Firm Performance on Manufacturing Companies - Dewi, Sari; Wijaya, Vieri (Fakultas Pendidikan Ekonomi dan Bisnis, 2021)
Abstract. This study aims to examine the effect of earnings management, board characteristics, and firm size on firm performance by measuring Tobin's Q (TQ). In this study, we examine the effect of earnings management using accrual-based earnings management and real earnings management, the effect of board characteristics using the variable the board of directors size and board of commissioners size, and also examine the effect of firm size by means of the natural log of firm assets. The results of this study indicate that accrual-based earnings management and firm size have a significant positive impact on firm performance while for real earnings management variables, the board of directors size, and the board of commissioners size are not significant on firm performance in this research topic.